Socioeconomic pattern of breastfeeding in sub-Saharan Africa: an individual participant data meta-analysis of six longitudinal cohorts - Alison Price; Clara Calvert; Suzanne Filteau; Laura Oakley; Judith R Glynn; Albert Dube; Milly Marston; Ronald Makanga; Shamsudeen Mohammed; Emily L Webb; Joseph O Mugisha (BMJ Public Health)
Background Breastfeeding rates in sub-Saharan Africa (SSA) are declining, and at the current rate, only four African countries will meet the WHO’s 2030 exclusive breastfeeding target. We examined the association between maternal socioeconomic status (SES) and breastfeeding practices in SSA.Methods Six cohorts in Ethiopia, Malawi, Uganda and Zambia, with 11 863 participants, were analysed. Data for the cohorts were collected between 2000 and 2021, covering births from 2000 to 2019. SES exposures were maternal education and household income. Breastfeeding outcomes included ever breastfed, early initiation of breastfeeding (Ethiopia only), exclusive breastfeeding for ≥4 months or ≥6 months, and continued breastfeeding for ≥1 year. Risk ratios from multivariable Poisson regression models for individual cohorts were pooled in a random-effects meta-analysis to assess the effects of SES on breastfeeding, adjusting for confounders.Results Meta-analysis found no evidence of a difference in ever breastfeeding between mothers with secondary or tertiary education and those with primary/no education. Mothers with secondary education (adjusted risk ratio (aRR)=1.11, 95% CI=1.01 to 1.21) and those from middle-wealth households (aRR=1.12, 95% CI=1.01 to 1.24) were more likely to initiate breastfeeding early than those with primary/no education or low household wealth, but there was no evidence of association in the tertiary education and higher-wealth groups. The association between maternal education and exclusive breastfeeding for ≥4 months and ≥6 months varied across cohorts, with no evidence of association in most cohorts. Overall, household wealth was not associated with exclusive breastfeeding for ≥4 months or ≥6 months. The meta-analysis showed no evidence of association between household wealth and breastfeeding for ≥1 year, but mothers with tertiary education were less likely (aRR=0.93, 95% CI=0.88 to 0.99) to breastfeed for ≥1 year than those with primary or no education.Conclusion We observed no clear socioeconomic pattern in breastfeeding, contrasting with patterns observed in high-income countries.